Funding for Performance and Equity: Student Success in English Further Education Colleges. - Jaquette, Ozan (Education Policy Analysis Archives, 2006)
The impact of performance funding on community college student outcomes is a contested issue. Performance funding policies in most U.S. states involve too small a proportion of funding to change college behavior. English further education colleges are similar to U.S. community colleges. 1992 policy reforms in England centralized policy control, and implemented a per-pupil funding formula; 10% of all funding is based on student success but other components of the funding formula pay colleges more money for enrolling disadvantaged students. This research uses five years of student level data to test the impact of these policies. Overall student success rates rose by 10% during the five-year period, with the largest gains made by ethnic minorities, adult basic education students, and students from disadvantaged neighborhoods. Although the English system depends on regulatory agencies that do not exist in the U.S., the major assertion of this research is that market-based funding policies˜if properly designed˜can promote equity in educational achievement.